Performance of bidimensional location quotients for constructing input-output tables - Xesús Pereira López; Napoleón Guillermo Sánchez-Chóez; Melchor Fernández (Journal of Economic Structures, 2021)
This article seeks to verify the extent to which the formulation of two-dimensional location quotients (2D-LQ) entails a methodological advance in building or generating economic accounts related to sub-territories drawing from basic information. The input-output tables of the Euro Area 19 for 2010 and 2015 are references for analysis. We have used five statistics to measure similarity between true domestic coefficient matrices for ten countries (Austria, Belgium, Estonia, France, Germany, Italy, Latvia, Slovakia, Slovenia, and Spain) and the matrices they generate using nonsurvey techniques (CILQ, FLQ, AFLQ, and 2D-LQ). The focus substantially centers on ranking methodological efficiency by comparing the results of the four techniques mentioned above. The scope of the work employs standard parameters (associated with 2D-LQ) as guidance to ascertain the optimum parameters.
Keywords: C13; C67; R19; 330; 2D-LQ; FLQ; Location quotients; Non-survey method; Regional input-output tables